Improvement of inactivated vaccine against porcine reproductive respiratory syndrome - D. A. Biruchenkov; Ye. P. Baborenko; Ye. A. Avsitidiysky; D. L. Dolgov; Zh. Yu. Muradyan; A. I. Albulov (Ветеринария сегодня)
The paper presents results of studying antigenicity and local tissue reaction in pigs immunized with the experimental PRRS vaccine produced on the basis of commercial SEPPIC (France) adjuvants with addition of water-soluble chitosan derivatives.